Allium elegantiflorum (A. sect. Codonoprasum, Amaryllidaceae), a unique new species from East Anatolia/Türkiye - Sağiroğlu, Mehmet; Bani̇, Bariş; Eker, İsmai̇l (Phytotaxa, 2026)
Allium elegantiflorum Eker, Bani & Sağıroğlu, a newly discovered species belonging to sect. Codonoprasum, is described and illustrated from Bingöl Province, Türkiye. It is a morphologically quite distinct species. Although it shares some similarities with A. tchihatschewii Boiss., A. armenum Boiss. & Kotschy ex Boiss. and A. bingoelense Yıld. & Kılıç, it is clearly distinguished from three species by the color of the outer tunic, the density of the umbel, the equal, spreading and short pedicels, the shape of the perigone, the color of the tepals with colorless midrib, the small tepals, the ovary shape and sizes, the capsule shape and width, and the small seeds. Furthermore, they are also distinguished from each other in terms of other characteristics specific to each species. Comprehensive information on its morphology, detailed illustration, ecology, distribution, conservation assessment, and taxonomic relationships is provided.